Statistical Study of Transformation Changes in the Ukrainian Economy - ZhuravlyovО. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The article deals with the economic diagnostics o f some important macroeconomic indicators o f Ukraine that will reveal the nature and speed o f the economic transformation. During the period o f2003-2007, the Ukrainian economy grew at an impressive pace. However, at present, the country is undergoing a period ofserious trials, it needs to address structural problems that endanger long-term economic growth. The way out o f the current situation should be the realization o f the potential for growth o f advanced sectors and increase o f productivity across the national economy. Special attention should be paid to the transition from extractive institutions to inclusive ones. Key factors in accelerating the Ukrainian economy are more vigorous fight against corruption and investment attraction. A set o f institutional variables is proposed, which allows for a more thorough assessment o f the nature o f economic transformation in Ukraine and detection o f such deviations - transformation o f the national economy occurs at different speeds. Along with the traditional shifts in the structure o f GDP (the dominating share o f services), there’s still insignificant statistical effect o f such important institutional categories as the level o f political globalization, the control o f corruption, the level ofproperty rights protection, the rule o f law, and the level o f social globalization.